2017
DOI: 10.1002/jemt.22950
|View full text |Cite
|
Sign up to set email alerts
|

Study of morphological and mechanical features of multinuclear and mononuclear SW480 cells by atomic force microscopy

Abstract: This article studies the morphological and mechanical features of multinuclear and mononuclear

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…For mononuclear cells, the distribution of those parameters was significantly different. The authors observed that multinuclear cells are more resistant to the fullerenol when compared with the mononuclear ones [201].…”
Section: Mechanobiology In Crc Therapeuticsmentioning
confidence: 97%
“…For mononuclear cells, the distribution of those parameters was significantly different. The authors observed that multinuclear cells are more resistant to the fullerenol when compared with the mononuclear ones [201].…”
Section: Mechanobiology In Crc Therapeuticsmentioning
confidence: 97%
“…For example, by combining AFM and confocal fluorescence microscopy, information on the mechanical properties of cells and tissues and fluorescence images can be obtained simultaneously 189 . Because AFM can detect changes in the mechanical properties of cells, it be used to observe the difference in cells before and after drug action, and play an important role in drug toxicity testing, drug development and drug screening [190][191] .…”
Section: Summary and Prospectsmentioning
confidence: 99%
“…The morphology and biomechanics of cells are important characteristics for distinguishing normal and damaged cells (Iyer et al, 2009; Lee & Lim, 2007; Murphy et al, 2013). In contrast to optical and electron microscopy, atomic force microscopy (AFM) can collect three‐dimensional images under near‐physiological conditions, enabling analysis of the morphology and mechanical properties of cells at the nanoscale (Balasuriya et al, 2012; Benitez & Toca‐herrera, 2014; He et al, 2018; Krieg et al, 2019; Liu et al, 2018; Rico et al, 2011). Cell biophysical properties are measured using AFM and recording the force–distance curve.…”
Section: Introductionmentioning
confidence: 99%